Integrated mass spectrometric and multivariate data analysis approaches for the discrimination of organic and conventional strawberry (Fragaria ananassa Duch.) crops. (November 2015) - D'Urso, Gilda; d'Aquino, Luigi; Pizza, Cosimo; Montoro, Paola
Abstract: In the present study, metabolic changes in secondary metabolites of Fragaria ananassa Duch. fruits during ripening were evaluated, and in particular, the differences between fruits obtained from either organic or conventional, non-organic crops. Extracts from ripe and unripe fruits of Fragaria ananassa var. Candonga were analyzed by direct infusion mass spectrometry using an instrument equipped with an ion trap analyzer (DI-ESI-IT-MS) and by liquid chromatography coupled to high resolution mass spectrometry using a mass spectrometer equipped with an ESI source and an Orbitrap analyzer (LC–ESI-FT-MS). Chromatograms were evaluated using the free software package MZmine and the resulting metabolomics data were processed. Data sets were analyzed by Principal Component Analysis (PCA) and Partial Least Squares Discriminant Analysis (PLS-DA). All the differences between the fruits collected from organic crops and conventional crops were underlined. In addition, LC–ESI-FT-MS analyses were useful to achieve a comprehensive characterization of metabolic profiles of strawberries (flavonoids, anthocyanins and catechins were identified in the extracts). Flavonoids and anthocyanins were present with similar metabolic profile in F. ananassa obtained from organic and conventional, non-organic crops with differences from ripe and unripe fruits. Phenolic compounds thus are not responsive for the classification observed by untargeted metabolomic approach. Highlights: Organic and conventional strawberry crops were discriminated based on metabolomics. DI-ESI-IT-MS with multivariate data analysis was used for fingerprint analysis. For the first time LC–ESI-FT (Orbitrap) MS was applied to Fragaria ananassa berry. DI MS fingerprint gave the same results of LC–MS in discrimination of crops.